2003
DOI: 10.1063/1.1603216
|View full text |Cite
|
Sign up to set email alerts
|

Strong Jahn–Teller effect in the excited state: Anomalous temperature dependence of the zero-phonon line

Abstract: We are studying the optical spectra of impurity centers in the case when the optical transition takes place between nondegenerate and two-fold degenerate electronic E-states characterized by a strong vibronic coupling. In the latter state the adiabatic surface has a shape of a deformed Mexican hat with three flat minima on the trough of the “hat.” We have found that in this case the usual T7-dependence of the homogeneous width of the zero-phonon line at low temperatures is replaced by a dependence close to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…An additional T 2 term has to be added to accurately describe the ensemble measurements at temperatures below 100 K, which might be associated with inhomogeneous broadening effects. According to Hizhnyakov et al [29][30][31] a T 4 law is expected for quadratic electron-phonon coupling of a 1g phonons and was also experimentally confirmed for SiV − centres [27]. In section 5 we present further evidence for the electron-phonon coupling of the optical transition being dominated by a 1g phonons.…”
Section: Snv Centressupporting
confidence: 61%
“…An additional T 2 term has to be added to accurately describe the ensemble measurements at temperatures below 100 K, which might be associated with inhomogeneous broadening effects. According to Hizhnyakov et al [29][30][31] a T 4 law is expected for quadratic electron-phonon coupling of a 1g phonons and was also experimentally confirmed for SiV − centres [27]. In section 5 we present further evidence for the electron-phonon coupling of the optical transition being dominated by a 1g phonons.…”
Section: Snv Centressupporting
confidence: 61%
“…Recently a theory was developed for accounting the influence of ͑pseudo-͒ Jahn-Teller effect on ZPL broadening. 27,28 It predicts approximately ⌫ ϳ T 3 -type dependence in a relatively wide temperature limits. Fitting our results with a function ⌫͑T͒ = ⌫ 0 + aT n resulted in a value of n close to 3 ͑see Fig.…”
mentioning
confidence: 95%
“…If the final state is dynamically unstable (here the frequency of the resonant mode is imaginary), then the broadening of the ZPL, induced by the vibronic interaction, does not tend to zero at T-0, resulting in the remarkable homogeneous width at T ¼ 0. The anomalous temperature dependence of ZPL of the described type has been observed in the optical spectra of NV centres in diamond [10][11][12], where this dependence was explained by the soft dynamics of the Mexican hat-type potential energy associated with the Jahn-Teller effect in the excited state.…”
Section: Introductionmentioning
confidence: 85%
“…In the case of the soft dynamics in the final state, which has previously been studied [10][11][12] , it was found that here ZPL is characterized by an anomalous temperature dependence: instead of the T 7 -type broadening in the low-temperature limit, one gets the T 3 -dependence; the T 4 -type temperature shift of the position of ZPL is also replaced by a much less dependent shift with temperature. If the final state is dynamically unstable (here the frequency of the resonant mode is imaginary), then the broadening of the ZPL, induced by the vibronic interaction, does not tend to zero at T-0, resulting in the remarkable homogeneous width at T ¼ 0.…”
Section: Introductionmentioning
confidence: 95%